Mesoporous N-rich carbon with single-Ni atoms as a multifunctional sulfur host for Li-S batteries - Li, Yunxiang (2023)
Physicochemical confinement and catalytic conversion of lithium polysulfides (LiPSs) are crucial to suppress the shuttle effect and enhance the redox kinetics of lithium-sulfur (Li-S) batteries. In this study, a NH4Cl-assisted pyrolysis strategy is developed to fabricate highly mesoporous N-rich carbon (designed as NC(p)) featuring thin outer shells and porous inner networks, on which single-Ni atoms are anchored to form an excellent sulfur host (designed as Ni-NC(p)) for Li-S batteries. During pyrolysis, the pyrolytic HCl from confined NH4Cl within ZIF-8 will in situ etch ZIF-8 to produce rich mesoporous in the carbonized product NC(p). The mesoporous Ni-NC(p) enables favorable electron/ion transfer, high sulfur loading, and effective confinement of LiPSs, while the catalytic effect of single-Ni species enhances the redox kinetics of LiPSs. As a result, the sulfur cathode based on the Ni-NC(p) host delivers obviously improved Li-S battery performance with high specific capacity, good rate capability, and cycling stability.